PENGARUH FRAUD DIAMOND DAN DAYA SAING TERHADAP KECURANGAN AKADEMIK MAHASISWA AKUNTANSI - RIA FEBRINA; MAPARDI MAPARDI; SARI SARI (JURNAL AKUNTANSI DAN KEUANGAN, 2022)
This study aims to find out and test empirically whether diamond fraud and competitiveness affects academic fraud of accounting students. In this study, the questionnaires distributed amounted to 100 questionnaires, the results of this study obtained pressure variables did not have a partial effect on academic cheating,opportunity variables have a partial effect on academic cheating, rationalization variables have no partial effect on academic cheating, ability variables have no partial effect on academic cheating. Competitiveness variables have no partial effect on academic cheating. Simultaneously variables of pressure, opportunity, rationalization, ability, and competitiveness have a simultaneous effect on academic cheating. Based on the results of the coefficient of determination (adjusted r square) test obtained a value of 0.447 or 44.7% affecting academic cheating, the remaining 55.3% was influenced by other variables that were not equalized in this research variable or influenced by other variables that were not studied.